Recurrent wheezing in very preterm infants. - Elder, D. E. (BMJ Group, 1996)
AIMS: To document the prevalence of, and identify risk factors for, recurrent wheezing treated with bronchodilators in the first year of life. METHODS: Parental history and neonatal data were collected prospectively in a regional cohort of very preterm infants (< 33 weeks). Data on maternal smoking, siblings at home, breast feeding, respiratory symptoms, and hospital re-admissions were documented at 12 months. RESULTS: Outcome data were available for 525/560 (95%) of survivors. The incidence of recurrent wheeze was 76/525 (14.5%) in very preterm infants and 20/657 (3%) in a cohort of term newborns. Significant risk factors for recurrent wheeze in very preterm infants were parental history of asthma, maternal smoking, siblings at home, neonatal oxygen supplementation at 28 days, 36, and 40 weeks of gestation. CONCLUSIONS: Wheezing respiratory illnesses are common in very preterm infants. The factors involved are similar to those in more mature infants, with the addition of immaturity and neonatal lung injury.